2003
DOI: 10.1016/j.adolescence.2003.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The causal ordering of mathematics anxiety and mathematics achievement: a longitudinal panel analysis

Abstract: Using data from the Longitudinal Study of American Youth (LSAY), we aimed to determine the causal ordering between mathematics anxiety and mathematics achievement. Results of structural equation modelling showed that, across the entire junior and senior high school, prior low mathematics achievement significantly related to later high mathematics anxiety, but prior high mathematics anxiety hardly related to later low mathematics achievement. Mathematics achievement was more reliably stable from year to year th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
291
2
25

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(372 citation statements)
references
References 35 publications
16
291
2
25
Order By: Relevance
“…However, the opposite pattern is also possible, i.e., failure in mathematics due to high general anxiety (see Carey, Devine, Hill, & Szűcs, 2017). Furthermore, in our study we matched our groups for general (trait) anxiety, and perhaps for this reason, in our MA-DD group, we selected only children who developed DD first and then subsequently developed state anxiety specifically related to mathematical tasks (see the Defict Thoery, Ma & Xu, 2004). Finally, although our findings seem to partially contradict previous results that indicated children with high MA showed WM impairments (Maloney, Risko, Ansari & Fugelsang, 2010), it is worth noting that the methodological differences between our study Where inhibitory mechanisms are concerned, we found that children with MA (but no DD) were more susceptible to proactive interference than the other three groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, the opposite pattern is also possible, i.e., failure in mathematics due to high general anxiety (see Carey, Devine, Hill, & Szűcs, 2017). Furthermore, in our study we matched our groups for general (trait) anxiety, and perhaps for this reason, in our MA-DD group, we selected only children who developed DD first and then subsequently developed state anxiety specifically related to mathematical tasks (see the Defict Thoery, Ma & Xu, 2004). Finally, although our findings seem to partially contradict previous results that indicated children with high MA showed WM impairments (Maloney, Risko, Ansari & Fugelsang, 2010), it is worth noting that the methodological differences between our study Where inhibitory mechanisms are concerned, we found that children with MA (but no DD) were more susceptible to proactive interference than the other three groups.…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, it was found out that students with low anxiety finished multidigit problems correctly per minute compared to the students with high anxiety (Cates & Rhymer, 2003). In an earlier study with a set of long-term trend data, Ma and Xu (2004a) found out that junior and senior high school students' former low performance in mathematics was significantly associated with future high mathematics anxiety. Conversely, the researchers reported that prior high mathematics anxiety was slightly associated with future low mathematics achievement.…”
Section: Mathematics Anxietymentioning
confidence: 99%
“…Trait math anxiety is assessed in the present study. Since low math scores could also lead to math anxiety (Ma and Xu 2004), a reciprocal relation between math performance and math anxiety can be assumed and is supported by meta-analysis (Hembree 1990).…”
mentioning
confidence: 99%